Political Leadership of Women in Nepal: A Critical Observation from the Local Elections 2022 - Sapkota, Mahendra (Journal of Political Science, 2024)
Women's representation in political leadership is crucial for liberal democracies. However, the persistent global gender gap in political participation raises important questions. This paper focuses on the state of women's political leadership in Nepal, using the 2022 local elections as a case study. It takes an epistemological critical approach and integrates quantitative and qualitative information from various secondary sources. The study reveals an increase in the number of women in leadership positions after the election, which can be attributed to the constitutional provisions of Nepal that aim to ensure inclusion, representation, and participation. However, these provisions do not guarantee the quality, competence, and empowerment of women in leadership roles, as they still face obstacles such as patriarchal structures, elitist-centric inclusive practices, and a lack of institutional support at the local level. This paper is valuable for those interested in political science, gender studies, or development studies.